2018
DOI: 10.1001/jamadermatol.2017.4701
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Preference-Based Quality-of-Life Measures for Economic Evaluations in Early-Stage Melanoma

Abstract: IMPORTANCE The diagnosis of a life-threatening disease like melanoma can affect all aspects of a person's life, including health-related quality of life (HRQOL) and psychological aspects of melanoma such as fear of cancer recurrence (FCR). Economic evaluations of psychological interventions require preference-based (utility) instruments that are sensitive to changes in well-being and HRQOL; however, very few studies have evaluated the sensitivity of these instruments when used for people with melanoma. OBJECTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…In a systematic review of 7 studies (4246 patients; 6 cross-sectional [3644], and 1 prospective study [45]), it was found that determinants of lower HRQOL (either psychological, physical, or global) were marital status, age, sex, poor social support, melanoma severity at diagnosis, and comorbidities (Table 3) [46]. Dieng et al found that HRQOL, measured with the Functional Assessment of Cancer Therapy (FACT-M), was correlated with fear of recurrence of disease in patients with metastatic melanoma (Table 3) [47]. A more comprehensive understanding of HRQOL can improve patient centered care in melanoma patients.…”
Section: Health Related Quality Of Life In Melanoma Survivorsmentioning
confidence: 99%
“…In a systematic review of 7 studies (4246 patients; 6 cross-sectional [3644], and 1 prospective study [45]), it was found that determinants of lower HRQOL (either psychological, physical, or global) were marital status, age, sex, poor social support, melanoma severity at diagnosis, and comorbidities (Table 3) [46]. Dieng et al found that HRQOL, measured with the Functional Assessment of Cancer Therapy (FACT-M), was correlated with fear of recurrence of disease in patients with metastatic melanoma (Table 3) [47]. A more comprehensive understanding of HRQOL can improve patient centered care in melanoma patients.…”
Section: Health Related Quality Of Life In Melanoma Survivorsmentioning
confidence: 99%
“… 10 Another study found that the Assessment of Quality of Life 8 Dimension Scale (AQoL-8D) to be more sensitive measure than others within context of economic evaluation of psychological interventions in melanoma. 51 Despite numerous challenges associated with collecting quality of life information in young and medically complex populations in a way that is suitable for inclusion in economic modelling, there remains extensive opportunity for improvement in these estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 20 full-text articles were screened and assessed for eligibility. Makady et al [30] was excluded for being a feasibility study using social media for measuring HRQOL, Swartz et al [31] was excluded for not using the established FACT-M questionnaire, and Davies et al [32] and Dieng et al [33] was excluded for not reporting any structured FACT-M data. See Fig.…”
Section: Literature Searchmentioning
confidence: 99%